Defining a national reference level for intraoperative radiation exposure in urological procedures: FLASH, a retrospective multicentre UK study. (19th September 2019) - Simson, Nick; Stonier, Thomas; Suleyman, Narin; Hendry, Jane; Salib, Miriam; Peacock, Julian; Connor, Martin; Jones, Oliver; Schuster‐Bruce, James; Bottrell, Oliver; Lovegrove, Catherine; English, Louise; et al.
Abstract : Objectives: To define reference levels for intraoperative radiation during stent insertion, ureteroscopy (URS), and percutaneous nephrolithotomy (PCNL); to identify variation in radiation exposure between individual hospitals across the UK, between low‐ and high‐volume PCNL centres, and between grade of lead surgeon. Patients/Subjects and Methods: In all, 3651 patients were identified retrospectively across 12 UK hospitals over a 1‐year period. Radiation exposure was defined in terms of total fluoroscopy time (FT) and dose area product (DAP). The 75th percentiles of median values for each hospital were used to define reference levels for each procedure. Results: Reference levels: ureteric stent insertion/replacement (DAP, 2.3 Gy/cm 2 ; FT, 49 s); URS (DAP, 2.8 Gy/cm 2 ; FT, 57 s); PCNL (DAP, 24.1 Gy/cm 2 ; FT, 431 s). Significant variations in the median DAP and FT were identified between individual centres for all procedures ( P  < 0.001). For PCNL, there was a statistically significant difference between DAP for low‐ (<50 cases/annum) and high‐volume centres (>50 cases/annum), at a median DAP of 15.0 Gy/cm 2 vs 4.2 Gy/cm 2 ( P  < 0.001). For stent procedures, the median DAP and FT differed significantly between grade of lead surgeon: Consultant (DAP, 2.17 Gy/cm 2 ; FT, 41 s) vs Registrar (DAP, 1.38 Gy/cm 2 ; FT, 26 s; P  < 0.001). Conclusion: This multicentre study is the largest of its kind. It provides the first national reference level to guide fluoroscopy use in urological procedures, thereby adding a quantitative and objective value to complement the principles of keeping radiation exposure 'as low as reasonably achievable'. This snapshot of real‐time data shows significant variation around the country, as well as significant differences between low‐ and high‐volume centres for PCNL, and grade of lead surgeon for stent procedures.